A review of botany, phytochemistry, pharmacology, and applications of the herb with the homology of medicine and food: Ligustrum lucidum W.T. Aiton - Chen, Liping; Huang, Dong; Jiang, Lin; Yang, Jihong; Shi, Xiaoyu; Wang, Rong; Li, Wenbin (Frontiers in Pharmacology, 2024)
Ligustrum lucidum W.T. Aiton is an outstanding herb with the homology of medicine and food. Its ripe fruits are traditionally used as an important tonic for kidneys and liver in China. Ligustrum lucidum W.T. Aiton is rich in nutritional components and a variety of bioactive ingredients. A total of 206 compounds have been isolated and identified, they mainly include flavonoids, phenylpropanoids, iridoid glycosides, and triterpenoids. These compounds exert anti-osteoporosis, anti-tumor, liver protective, antioxidant, anti-inflammatory, and immunomodulatory effects.Ligustrum lucidum W.T. Aiton has been traditionally used to treat many complex diseases, including osteoporotic bone pain, rheumatic bone, cancer, related aging symptoms, and so on. In the 2020 Edition of Chinese Pharmacopoeia, there are more than 100 prescriptions containing Ligustrum lucidum W.T. Aiton. Among them, some classical preparations including Er Zhi Wan and Zhenqi fuzheng formula, are used in the treatment of various cancers with good therapeutic effects.Additionally, Ligustrum lucidum W.T. Aiton has also many excellent applications for functional food, ornamental plants, bioindicator of air pollution, algicidal agents, and feed additives. Ligustrum lucidum W.T. Aiton has rich plant resources. However, the application potential of it has not been fully exploited. We hope that this paper provides a theoretical basis for the high-value and highconnotation development of Ligustrum lucidum W.T. Aiton in the future.